Incorporation of growth factor loaded microspheres into polymeric electrospun nanofibers for tissue engineering applications - Gungor-Ozkerim, P. Selcan; Balkan, Timucin; Kose, Gamze T.; Sarac, A. Sezai; Kok, Fatma N. (Wiley, 2013)
AbstractNanofibrous double‐layer matrices were prepared by electrospinning technique with the bottom layer formed from PCL (poly‐ε‐caprolactone)/PLLA (poly‐l‐lactic acid) nanofibers and the upper layer from PCL/Gelatin nanofibers. Bottom layer was designed to give mechanical strength to the system, whereas upper layer containing gelatin was optimized to improve the cell adhesion. Gelatin microspheres were incorporated in the middle of two layers for controlled growth factor delivery. Successful fabrication of the blend nanofibers were shown by spectroscopy. Scanning electron microscopy results demonstrated that bead‐free nanofibers with uniform morphology could be obtained by 10% w/v concentrations of PCL/PLLA and PCL/Gelatin solutions. Microspheres prepared by 15% gelatin concentration and cross‐linked with 7.5% glutaraldehyde solution were chosen after in vitro release studies for the incorporation to the double‐layer matrices. The optimized conditions were used to prepare fibroblast growth factor‐2 (FGF‐2) loaded microspheres. Preliminary cell culture studies showed that the FGF‐2 could be actively loaded into the microspheres and enhanced the cell attachment and proliferation. The complete system had a slow degradation rate in saline (18% weight loss in 2 months) and it could meanwhile preserve its integrity. This sandwich system prevented microsphere leakage from the scaffold, and the hydrophilic and bioactive nature of the fibers at the upper layer promoted cell attachment to the surface. PLLA/PCL layer, on the other hand, improved the mechanical properties of the system and enabled better handling. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 1897–1908, 2014.
Keywords: Drug Carriers; Osteoblasts; Tissue Engineering; Tissue Scaffolds; Polymers; Polyesters; Nanofibers; Cell Line; Gelatin; Humans; Fibroblast Growth Factor 2; Lactic Acid; Cell Proliferation